DAMPAK ISLAMIC CORPORATE SOCIAL REPORTING DAN STRUKTUR KEPEMILIKAN TERHADAP PENGHINDARAN PAJAK - Alvita Tyas Dwi Aryani; Riska Naila Zulfa; Muhammad Nur Fathoni (Universitas Budi Luhur, 2024)
This quantitative study aims to examine the impact of Islamic Corporate Social Responsibility (ICSR) and ownership structure on tax avoidance. The research population consists of companies listed on the Jakarta Islamic Index (JII) for the period 2019-2023, with a sample of 60 companies selected using purposive sampling. The structural model was tested using the SmartPLS application. The results indicate that ICSR, managerial ownership, and government ownership have a negative effect on tax avoidance. Conversely, foreign ownership and institutional ownership do not have a significant impact on tax avoidance. The negative influence of ICSR and managerial ownership suggests that companies applying Islamic values and having strict oversight tend to be more compliant with tax obligations. On the other hand, the lack of significance for foreign and institutional ownership may be due to a focus on profitability and limited involvement in tax policies.